Math, asked by gourinadhsurya, 9 months ago

please solve that triganomatry problem....​

Attachments:

Answers

Answered by LaeeqAhmed
1

Step-by-step explanation:

GIVEN,

 \frac{ \cos(37) +  \sin(37)  }{ \cos(37)  -  \sin(37)  }

 =  \frac{ \cos(90 -53) + \sin(37)   }{ \cos(90 - 53) -  \sin(37)  }

 =   \frac{ \sin(53) +  \sin(37)  }{ \sin(53) -  \sin(37)  }

 =  \frac{2 \sin( \frac{53 + 37}{2})  \cos(  \frac{53 - 37}{2}  ) }{2 \sin( \frac{53 - 37}{2} ) \cos( \frac{53 + 37}{2} )  }

 =  \frac{ \sin(45) \cos(8)  }{ \sin(8) \cos(45)  }

 =  \tan(45)  \cot(8)

 = 1  \times  \cot(</strong><strong>8</strong><strong>)

 =  \cot(</strong><strong>8</strong><strong>)

HOPE THAT HELPS!!

Similar questions